Rheumatology in Practice - Pereira da Silva, Jose Antonio; Woolf, Anthony D.; SpringerLink (Online service) (London : Springer London, 2010)
Rheumatology in Practice offers chapters which are organised and built around anatomical and regional syndromes, so reinforcing the evidence-based approach. As readers progress through the text they are given more demanding and challenging questions, encouraging them to use their diagnostic skills to identify the main syndromes and the underlying diseases responsible for the disorders in question. The text is lavishly illustrated in full colour, with detailed photos of patient examinations, complemented by radiographs and full colour line illustrations. The text also benefits from the use of summaries using coloured boxing to identify key points in diagnosis and management. Written by two of the most respected clinicians in the discipline, this book will be essential reading for rheumatologists in practice and training.
The Importance of Rheumatic Diseases -- Pain, Disease and Suffering an Integrated Perspective -- The Structure and Function of the Musculoskeletal System Sources of Pain -- Diagnostic Strategy the Main Syndromes in Rheumatology -- The Standard Enquiry in Rheumatology -- The General Clinical Examination -- Regional Syndromes Neck pain -- Regional Syndromes The Painful Shoulder -- Regional Syndromes The Elbow And Forearm -- Regional Syndromes the Wrist and Hand -- Regional Syndromes Low Back Pain -- Regional Syndromes The Hip -- Regional Syndromes The Knee -- Regional Syndromes the Foot and Ankle -- Generalized Pain Syndrome Fibromyalgia -- Osteoarthritis -- Inflammatory Arthritides Diagnostic Strategies -- Monoarthritis -- Chronic, Additive, Symmetrical, Peripheral Polyarthritis -- Chronic, Asymmetrical Oligo- Or Polyarthritis -- Chronic Proximal Oligoarthritis -- Arthritis of the Shoulder and Pelvic Girdles Polymyalgia Rheumatica -- Acute Oligo- or Polyarthritis Febrile Arthritis Arthritis with Mucocutaneous Manifestations -- Inflammatory Low Back Pain -- Systemic Syndromes Connective Tissue Diseases Vasculitis Raynaud$1 (Bs Phenomenon -- Osteoporotic Syndrome Osteoporosis -- Bone Syndrome Bone Diseases -- Rheumatic Symptoms in Children and Adolescents -- Treating Rheumatic Diseases -- Drugs Commonly Used in Rheumatic Diseases.s
Keywords: Medicine; Internal medicine; Rheumatology; Medicine & Public Health; Rheumatology; Internal Medicine